Evaluation of activated carbon fiber packed-bed for the treatment of gas-to-liquid wastewater: experimental, modeling and ASPEN Adsorption simulation - Roghayeh Yousef (16442150) (2024)
This study investigates the continuous adsorption treatment of gas-to-liquid (GTL) wastewater from the Fischer-Tropsch process using activated carbon fiber (ACF) as the adsorbent. ACF, characterized by a high surface area of 1232 m²/g, was utilized to treat actual GTL wastewater, which contains long and short-chain alcohols, fatty acids, and other hydrocarbons. Experimental analysis, packed-bed modeling and simulation using ASPEN Adsorption were employed to understand the dynamics of the adsorption process. The experimental setup involved a bench-scale column packed with specified masses of ACF, with GTL wastewater pumped upward through the column at varying flow rates. Breakthrough curves were constructed to assess column performance, with parameters, such as feed flow rate (5 and 10 mL/min) and packing mass (5 and 10 g) systematically varied. The results demonstrate a significant influence of these parameters on column performance, with higher flow rates initially accelerating adsorption kinetics. Conversely, increasing packing mass extends the duration of column saturation, improving efficiency. Empirical models, including the Yoon-Nelson and El-Naas et al. models were applied to fit the experimental data, with the latter showing superior performance in representing the adsorption mechanism within the column. Quantitative analysis of model fitting using Akaike Information Criteria (AIC) identified the Yoon-Nelson and El-Naas et al. model as the most suitable for describing the GTL wastewater/ACF system, with an AIC weight parameter of 0.33 and R2 averaging 86.5%. Furthermore, simulation results from ASPEN Adsorption exhibited strong agreement with experimental data, validating its efficacy for simulating liquid adsorption processes. The study provides valuable insights into the design and optimization of large-scale wastewater treatment systems, offering practical solutions to address global water challenges. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-024-00846-3